Constructing a dual-path motivation-regulation model of elderly sport consumption: a psychological perspective on behavioral drivers - Zhou, Chong; Xu, Zehan; Shi, Xiao; Liu, Heng; Chen, Yuanxin (Frontiers in Psychology, 2025)
This paper presents a dual-path motivation-regulation framework for elderly sports consumption, aimed at comprehensively revealing how intrinsic motivation and external regulatory mechanisms jointly influence the behavioral decisions of older adults in sports consumption. The framework integrates Self-Determination Theory (SDT), Expectancy-Value Theory (EVT), and the Social Ecological Model (SEM), outlining two major paths: the motivation path and the regulation path. The motivation path highlights the internal psychological needs and emotional identification that drive elderly individuals in their sports consumption decisions. Key factors include consumer autonomy, perceived competence, emotional recognition, and motivational differentiation. The regulation path emphasizes the role of external factors such as family and social support, policy incentives, cultural identity, and product-market fit in shaping consumption behaviors. This paper also discusses the dynamic interaction and feedback loop between these two paths, showing that external regulatory factors can enhance intrinsic motivation, while intrinsic motivation can sustain consumption behavior despite weak external support. In conclusion, the paper provides policy and practical recommendations, focusing on strengthening intrinsic motivation through autonomy and confidence-building, enhancing external regulation through supportive family, institutional, and cultural frameworks, and adapting the market to better meet elderly consumers’ needs. This study offers a theoretical foundation for promoting elderly sports consumption and provides actionable insights for policymakers, social organizations, and commercial entities to foster long-term engagement and development in elderly sports consumption.